Community Empowerment Through Legal Counseling: Increasing Legal Awareness and Justice for Women and Children in Cijeruk Hamlet, Tasikmalaya City - Sidiq, Fahmi; Wang, Chun; Laksito, Grida Saktian (International Journal of Research in Community Services, 2024)
Legal education about justice for women and children is an important step in understanding the Cijeruk Hamlet community about the rights and obligations of women and children in a legal context. This activity aims to fill this gap in understanding and increase understanding about the equal rights and obligations of women and children. In this activity, Article 30 of Law Number 1 of 1974 concerning Marriage was socialized as a legal basis that guarantees equal rights for women and children. This activity also involved PKK women in Cijeruk Village, who have an important role in spreading information and understanding about justice for women and children in their environment. In addition, group counseling is carried out to provide opportunities for group members to share knowledge and experiences in overcoming family problems. The result of this legal education activity is an increase in public awareness, especially PKK women, about the rights and obligations of women and children under the law. The impact is the formation of a women's group that cares about justice for women and children.